IMPROVED ABILITY DIFFERENCE RESOLUTION MATH STUDENTSUSING PBL LEARNING MODEL WITH INKUIRI ON MATERIALS CUBE AND BEAM IN SMP 6 MEDAN - Arifin Azhari Harahap; Sahat . Saragih (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2019)
ABSTRACTThis study attempts to find out if the ability of problem solving math students who had learning problem based on the model of  PBL higher than on the ability of the solution that will teach with inkuiri learning model to the matter of the cube and beams in class VIII 6’Junior High School medan and to know the resolutions of the related problem solving ability students who had learning pbl and inkuiri with cube and beams in VIII 6’Junior High School  Medan. This research is experiment. Population in this research were all students 6’JuniorHigh School Medan. The data were analyzed using the SPSS.Studies show that there are differences increased capacity problem solving math students who had learning model with pblwith  inkuiri solving and math skills students who had learn with PBL learning model is better than Inkuiri. Keywords: Problem Solving Ability, Cube and Beams, Problem Based Learning (PBL), Inkuiri  ABSTRACTThis study attempts to find out if the ability of problem solving math students who had learning problem based on the model of  PBL higher than on the ability of the solution that will teach with inkuiri learning model to the matter of the cube and beams in class VIII 6’Junior High School medan and to know the resolutions of the related problem solving ability students who had learning pbl and inkuiri with cube and beams in VIII 6’Junior High School  Medan. This research is experiment. Population in this research were all students 6’JuniorHigh School Medan. The data were analyzed using the SPSS.Studies show that there are differences increased capacity problem solving math students who had learning model with pblwith  inkuiri solving and math skills students who had learn with PBL learning model is better than Inkuiri. Keywords: Problem Solving Ability, Cube and Beams, Problem Based Learning (PBL), Inkuiri